Autonomous flight control system designed for small-scale helicopter based on approximate dynamic inversion - Zhiyang Zhang; Fei Hu; Jian Li (2011 3rd International Conference on Advanced Computer Control, 2011)
This paper describes the development of an autonomous flight control system for small-scale unmanned helicopter based on approximate dynamic inversion (ADI) method. The flight controller consists of inner-loop attitude control, mid-loop velocity control and outer-loop position control. Previous researches have shown that for minimum-phase, nonaffine-in-control system, Proportional-Integral (PI) controller is an equivalent realization of ADI control law in time response. In this paper, we also design a PI controller to verify this statement in the Yamaha R50 UAV helicopter model and then compare the two control methods' performance and features using flight data obtained in simulation. Simulation results show that both ADI and PI control approaches achieve excellent performance. The autonomous flight control system designed in this paper successfully drives the helicopter to fly autonomously and execute flight missions.